PENGARUH PERENCANAAN TATA RUANG KANTOR TERHADAP PRODUKTIVITAS PEGAWAI DI BAGIAN ADMINISTRASI PEREKONOMIAN SEKRETARIAT DAERAH KOTA CIREBON - Yuhan Ditra; Hery Nariyah; Amanan . (Universitas Swadaya Gunung Jati, 2016)
Abstrak A research writer do is the influence of spatial planning of the office against labor productivity employees in the administration of the economy of the secretariat of the city of Cirebon. A problem which the author told labor productivity is employees in economic administrasi the regional secretariat of cirebon city still low, it is alleged that the problem caused by spatial planning of the office of ineffective.Research methodology who writers do is quantitative research methodology, where starting from collecting data, of interpretation of data, until the result of his research use numbersResearch questions submitted, is the influence of spatial planning by the head office part against labor productivity employees.A hypothesis that is in order following “Allegedly there is a significant positive effect of the spatial planning and the office of the chief of staff of the Secretariat of the Local Administration, Cirebon City”Of hypotheses it can be formulated hypothesis statistic i.e. H0 ( hypothesis zero ): rs count “of rs table, hence the formulation the problem is “there is no positive influence and significant between spatial planning of of office by the head of labor productivity of employees in economic administrasi regional secretariat of cirebon city.” and Ha ( of alternative hypotheses ): rs count & gt; of rs table, hence the formulation the problem is “there are the influence of a positive and significant between spatial planning of of office by the head of labor productivity of employees in economic administrasi regional secretariat of cirebon city”.In research results obtained that spatial planning office done by the head of administration regions economy secretariat of the city of cirebon has is good enough but not optimal as is apparent from the success of spatial planning of the office that 53 % with a score of 412, total and labor productivity employees have good enough but still low as 53 % with a total score 412. The implementation of the spatial planning of the head of the office part by having influence that tightly against labor productivity employees in part economic administration secretariat of the city of cirebon regions with a value of rs count 0,876 and if in rs compare with table worth 0,464. Because rs count larger than rs table, there is the influence of a positive and significant between spatial planning of of office by the head of labor productivity of employees in economic administrasi regional secretariat of cirebon city .Thus h0 ( hypothesis zero ) were rejected and ha ( of alternative hypotheses ) accepted.